LED Light Increases Leaf Area and Root Length of Humulus lupulus (var. Tettnanger) In Vitro - Chi Dinh Nguyen; Dominic Vu; Heqiang Huo; Brian Pearson (EDIS)
Propagation of hops has traditionally been accomplished through vegetative techniques. A more modern technique, micropropagation, can be used to propagate hops and offers several advantages to vegetative techniques. Research examining the use of LED lights in plant production has observed its ability to promote growth in plants through emission of higher light quality, such as enhanced red and blue wavelength discharge. This new 5-page EDIS publication provides information on the use and application of LED lights to enhance leaf area and root length of hops. Written by Chi D. Nguyen, Dominic Vu, Heqiang Huo, and Brian Pearson, and published by the UF/IFAS Environmental Horticulture Department. https://edis.ifas.ufl.edu/ep583